VD_FINDINFO Décision / 2013 / 25 vom 29. August 2012 - VD Tribunal cantonal (2012)
SÉQUESTREMESURE PROVISIONNELLE, CONNEXITÉ MATÉRIELLE | 71 al. 3 CP, 263 al. 1 let. b CPP (CH), 393 al. 1 let. a CPP (CH)